Pengaruh profitabilitas (ROA), likuiditas (CR), dan solvabilitas (DER) terhadap nilai perusahaan yang terdaftar di Bursa Efek Indonesia - Viola Karenina Sinaga; Stefani Inda Sari; Eric Halim; Mariska Sisilia (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to examine the effect of profitability, liquidity, and solvency partially and simultaneously on the value of companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2019. The research sample was 27 companies which were selected using purposive sampling. The study found that all variables simultaneously had a significant effect on firm value. However, partially none of the variables affect the value of the company's consumer goods industry sector.